Elevated serum interleukin‐2 after gluten correlates with symptoms and is a potential diagnostic biomarker for coeliac disease. Issue 8 (4th September 2019) - Tye‐Din, Jason A.; Daveson, A. James M.; Ee, Hooi C.; Goel, Gautam; MacDougall, James; Acaster, Sarah; Goldstein, Kaela E.; Dzuris, John L.; Neff, Kristin M.; Truitt, Kenneth E.; Anderson, Robert P.
Summary: Background: Coeliac disease patients on a gluten‐free diet experience reactions to gluten, but these are not well characterised or understood. Systemic cytokine release was recently linked to reactivation of gluten immunity in coeliac disease. Aim: To define the nature and time‐course of symptoms and interleukin‐2 changes specific for coeliac disease patients. Methods: 25 coeliac disease patients on a gluten‐free diet and 25 healthy volunteers consumed a standardised 6 gram gluten challenge. Coeliac Disease Patient‐Reported Outcome survey and global digestive symptom assessment were completed hourly up to 6 hours after gluten. Adverse events over 48 hours were recorded. Serum interleukin‐2 was measured at baseline, and 2, 4 and 6 hours. Results: Serum interleukin‐2 was always undetectable in healthy controls, whereas it was undetectable at baseline and elevated >0.5 pg/ml at 4 hours in 92% of coeliac disease patients. All patient‐reported outcome severity scores increased significantly after gluten in coeliac disease patients ( P < .001 Wilcoxon signed rank test), but not in controls. Symptoms began after 1 hour, and peaked in the third. Nausea and vomiting characterised severe reactions, but mild reactions were limited to headache and tiredness. Peak interleukin‐2 correlated with symptom severity, particularly for nausea and vomiting. Conclusions: Serum interleukin‐2 elevations correlate with timing and severity of symptoms after gluten in coeliac disease. Standardised bolus gluten food challenge and interleukin‐2 assessment could provide a valuable clinical test to monitor and diagnose coeliac disease in patients established on a gluten‐free diet.